2019
DOI: 10.3390/ijms20092054
|View full text |Cite
|
Sign up to set email alerts
|

The Water Extract of Juniperus communis L. Induces Cell Death and Sensitizes Cancer Cells to Cytostatic Drugs through p53 and PI3K/Akt Pathways

Abstract: Juniper (Juniperus communis L.) is a northern coniferous plant generally used as a spice and for nutritional purposes in foods and drinks. It was previously reported that juniper extract (JE) affects p53 activity, cellular stress, and gene expression induced cell death in human neuroblastoma cells. Therefore, the effects of juniper on p53 and Akt signaling was examined further in A549 lung, 22RV1 and DU145 prostate, and HepG2 liver cancer cells using Western blot, confocal microscopy, and MTT analysis. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…NFκB activation induces the expression of cytokines, such as TNF‐α, IL‐1β, and IL‐6, and chemokines, such as CCL2 (Liu et al, 2017). In one study, a water JCo extract inactivated the PI3K–Akt pathway in cancer cells (Raasmaja et al, 2019), and our data revealed that JCo extract suppressed NFκB expression and the downstream expression of chemokines and cytokines such as TNF‐α, IL‐1β, IL‐6, and CCL2 in the rat renal cell line NRK‐52E. In addition to the inflammatory response, LPS induced IL‐1β mRNA expression, controlled by nod‐like receptor protein 3 inflammasome, which is involved in the AMPK–ROS signaling pathway (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…NFκB activation induces the expression of cytokines, such as TNF‐α, IL‐1β, and IL‐6, and chemokines, such as CCL2 (Liu et al, 2017). In one study, a water JCo extract inactivated the PI3K–Akt pathway in cancer cells (Raasmaja et al, 2019), and our data revealed that JCo extract suppressed NFκB expression and the downstream expression of chemokines and cytokines such as TNF‐α, IL‐1β, IL‐6, and CCL2 in the rat renal cell line NRK‐52E. In addition to the inflammatory response, LPS induced IL‐1β mRNA expression, controlled by nod‐like receptor protein 3 inflammasome, which is involved in the AMPK–ROS signaling pathway (Wang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Juniperus communis oil contains monoterpene hydrocarbons, such as α‐pinene, myrcene, sabinene, and β‐pinene (Bais et al., 2014; Cabral et al., 2012; Hajdari et al., 2015), most of which are polyphenolic compounds, indicating their anti‐cancer potential. Studies have shown that Juniperus communis L. berry water extracts induces p53‐associated cell apoptosis in human SH‐SY5Y neuroblastoma cells (Lantto et al., 2016), and increases the effect of 5‐FU in non‐small lung cancer A549 cells through regulation of AKT phosphorylation (Raasmaja et al., 2019). In addition, juniper berry oil from Juniperus communis is a chemo‐preventive dietary agent that inhibits cell proliferation and inflammation and induces apoptosis, resulting in suppression of colon tumor formation in azoxymethane‐treated rats (Yaman et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, studies advocate impact of anti‐cancer agents in impairing PI3K/Akt signaling in prostate cancer suppression (Fig. 5) (Abd Wahab et al 2021; Li et al 2018a, b, 2020; Long et al 2021; Zhang et al 2021a, b, c; Chan et al 2017; Raasmaja et al 2019; Sachan et al 2018).…”
Section: Anti‐cancer Drugsmentioning
confidence: 99%